Heavy-ion beam irradiation inhibits invasion of tongue squamous cell carcinoma Tca8113 cells - Feng, Zhenghu (Oncol Lett, 2019)
Tongue squamous cell carcinoma (TSCC) is a common malignant tumor type with aggressive biological characteristics, located in the oral and maxillofacial region. Vascular endothelial growth factor (VEGF) and matrix metalloproteinases (MMPs) have been implicated in the invasion and metastasis of various malignant tumor types, such as lung cancer and gastric carcinoma. High linear energy transfer (LET) particle irradiation has several advantages over conventional X-rays in suppressing the invasion and metastasis of malignant tumors. The objective of the present study was to investigate the effects of high-LET carbon ions and low-LET X-rays on the expression of VEGF and MMPs, and to identify the associated mechanisms in the Tca8113 TSCC cell line. Tca8113 cells were irradiated with carbon ions or X-rays at doses of 1 and 4 Gy. An immunofluorescence assay indicated that VEGF expression was notably decreased at 24 and 48 h after heavy ion irradiation compared with irradiation with conventional X-rays. The expression of MMP-2 and MMP-9 also decreased in a dose-dependent manner following heavy ion irradiation. These findings indicate that compared with low-LET X-ray irradiation, high-LET carbon ions possess higher biological efficacy in inhibiting the invasive ability of Tca8113 cells via reduction of VEGF, MMP-2 and MMP-9 expression.